Nanoemulsion of myricetin enhances its anti-tumor activity in nude mice of triple-negative breast cancer xenografts - Sharma, Preeti; Rai, Yogesh; Khan, Mohammad Ahmed; Bhatt, Anant Narayan; Najmi, Abul Kalam; Chaturvedi, Shubhra; Akhtar, Mohd.; Mishra, Anil Kumar (Frontiers in Oncology, 2025)
PurposeMyricetin, a naturally occurring flavonoid exhibits good anti-cancer properties. However, its practical application is limited due to poor aqueous solubility and low bioavailability. To overcome these challenges, a nanoemulsion-based formulation of myricetin was developed and its anti-tumor efficacy was compared with Myricetin alone in TNBC xenografts.MethodsAthymic nude mice were randomly divided into three groups (n=8) of control, Myricetin (50mg/kg), Myr-NE (25mg/kg), and subcutaneously implanted with MDA-MB-231 cells. After the 7-day treatment regimen, tumor volume was measured for up to 21 days, followed by mechanistic investigation, including tumor histology and immunoblotting. Tumor migration, invasion, cell proliferation kinetics, clonogenic, oxidative stress, and nuclear fragmentation studies were performed in tumor-derived cells. ANOVA test was further performed for statistical analysis to assess the significance between the experimental groups.ResultsMyr-NE treatment substantially reduced tumor progression compared to Myricetin alone in TNBC xenografts. The invasion, proliferation, and clonogenicity of Myr-NE tumor-derived cells were significantly reduced compared to Myricetin. The mechanistic investigation revealed that Myr-NE treatment effectively inhibits the PI3K/AKT/mTOR signaling and VEGFR2, accompanied by a significant reduction in the level of tumorigenic factors, including HIF-1α, Ki67, and MMP9 proteins compared to Myricetin. Myr-NE treatment also showed increased oxidative stress and DNA damage, resulting in enhanced tumor cell death compared to Myricetin alone.ConclusionSimilar to our earlier observation in in-vitro TNBC model, findings in the present study highlights that nanoemulsion of myricetin potentiates its anti-tumor activity in TNBC xenografts and provide a promising drug delivery strategy for better clinical outcomes.